Assessment of pumpkin (Cucurbita sp.), poppy (Papaver somniferum L) and sunflower (Heliantus annus L) seeds based on their mineral profile - Bolaños, Daniela (2019)
A multivariate analysis was performed on sunflower, poppy and pumpkin seeds based on the analysis of 18 elements including Al, As, B, Ba, Ca, Cd, Cu, Fe, K, Mg, Mn, Na, P, Pb, Si, Sr, Ti, and Zn which were quantified using microwave induced plasma optical emission spectrometry (MIP-OES). To avoid geographical effects, all samples were collected from the same region -San Luis province, Argentina- from 2016 to 2017. In order to determine differences in the mineral profiles as well as to get information from its mineral status, principal component analysis (PCA) was applied. In accordance with this study, toxic elements as pb, cd and as were not detected in the analyzed species, which is a remarkable point compared with other regions around the world. Furthermore, high levels of non-essential nutrients (Al, Ba and Sr) as well as those considered as beneficial non-essential nutrients (Si and Ti) were found in poppy. Applying multivariate analysis -performed by principal components analysis, PCA- it was possible to discriminate groups of seeds according to their botanical origins. Furthermore, PCA allowed inferring about the effect on seed quality due presence of Al, Ba or Sr, as well as the selectivity mechanisms of mineral uptake and filling seed and the differential performance of seeds for initial plant growth -due Si and Ti content- on the three studied species. For these reasons, multivariate analysis has been useful as an informative tool for ionomic and plant development studies.